INTERACTION OF COMPOSITE FILLING MATERIALS WITH MICROORGANISMS IN THE ORAL CAVITY - Davlatbaev Khasan Makhmudovich; Khabibova Nazira Nasullaevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation. This article mouth space microflora composite filler materials to the surface adhesion to oneself typical features studies. in the study various kind composite filler of materials to bacteria relatively adhesion level and this of the process biological effects analysis the materials were chemical composition, surface structure and microscopic features bacteria filler to the surface to stick how impact to show determined. nanocomposite materials bacteria high at the level to oneself attraction did if, microfill composite materials and less adhesion indicators demonstration the research results, composite filler of materials microorganisms with mutual connection reduce for new antibacterial technologies working exit the necessity shows. this article in dentistry composite materials optimization and microflora healthy balance storage for important scientific the basics presented will reach.